Determinants of financial literacy among Thai undergraduates for digital and adaptive learning design - Pichit Boonkrong; Makusee Masae; Teerawat Simmachan; Chuleekorn Nuansomsri (Institute of Advanced Engineering and Science, 2026)
This study examines the relationship between academic performance and financial literacy among 618 undergraduate students at Rangsit University, drawn from a population of 28,068 students using convenience sampling between June and December 2024. A mixed-methods design was employed, integrating Organisation for Economic Co-operation and Development (OECD-aligned) questionnaires with in-depth interviews of 10 students to capture both quantitative patterns and qualitative perspectives. Statistical analyses at the 0.05 level indicated that academic year, grade point average-cumulative (GPAX), field of study, financial education background, income source, and income level significantly predicted financial literacy outcomes. Students with higher GPAX showed stronger financial knowledge and behavior, although financial attitudes were slightly weaker. Health-science students demonstrated the highest literacy levels, followed by those in business, engineering, and social sciences. Income level influenced financial behavior but showed limited effects on attitudes, while prior financial education modestly improved knowledge with minimal behavioral impact. More than half of participants exhibited weak understanding of compound interest, limiting long-term saving capability. Insights from interpretative phenomenological analysis (IPA) and digital-learning perspectives underscore the need for context-responsive and technology-enhanced financial education. Therefore, the findings highlight how academic and socioeconomic factors shape financial literacy and offer guidance for developing personalized curricula and digital interventions aligned with sustainable development goals (SDGs) 1, 4, 8, and 10.